Toward a Geography of Black Internationalism: Bayard Rustin, Nonviolence, and the Promise of Africa. Issue 6 (1st November 2016) - Hodder, Jake
Abstract : This article charts the trip made by civil rights leader Bayard Rustin to West Africa in 1952 and examines the unpublished Africa Program that he subsequently presented to leading U.S. pacifists. I situate Rustin's writings within the burgeoning literature on black internationalism that, despite its clear geographical registers, geographers themselves have as yet made only a modest contribution toward. The article argues that within this literature there remains a tendency to romanticize cross-cultural connections in lieu of critically interrogating their basic, and often competing, claims. I argue that closer attention to the geographies of black internationalism, however, allows us to shape a more diverse and practiced sense of internationalist encounter and exchange. The article reconstructs the multiplicity of Rustin's black internationalist geographies that drew eclectically from a range of pan-African, American, and pacifist traditions. Although each of these was profoundly racialized, each conceptualized race in distinctive ways and thereby had differing understandings of what constituted the international as a geographical arena. By blending these forms of internationalism, Rustin was able to promote a particular model of civil rights that was characteristically internationalist in outlook, nonviolent in principle, and institutional in composition, a model that in selective and uneven ways continues to shape our understanding of the period.